Analisis Nilai Tambah Usaha Kopra di Desa Karya Bhakti Kecamatan Kulisusu Barat Kabupaten Buton Utara - Trisutrisno, Sunoko Bambang; Geo, La Ode; Limi, Muhammad Aswar (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This study aims to analyze the level of value added and income of the coconuts into copra processing business in Karya Bhakti village West Kulisusu District, North Buton. This study was conducted in December 2016 to February 2017. The determination of the study area based on the consideration that, in the village there is a population that has already been doing copra business and more numerous than the other villages in West Kulisusu District. Respondents in this study are 8 copra businessmen in Karya Bhakti village. Respondents in this study were purposively determined. Data analysis used is analysis of value added and income. The result shows that coconuts into copra processing business contributed Rp. 653.125 revenues in a single production process and create value added amounted to Rp. 2.805, 7/ Kg raw material. Ratio of value added to the product value is amounted to 47.76%. This means that for every Rp. 100 value added will earn Rp. 47.76 product value. The value added showed a great value. This is due to the high value of the product, while the prices of raw materials and other inputs donations are not too large